Answer:
3
Step-by-step explanation:
f(x) =2x+3
Let x=0
f(0) =2*0+3
Multiply
f(0) =0+3
Add
f(0) =3
<span>Leah, Let x=Blair's fish and 2x= Jay's fish; yet together they caught 27 fish. So, x + 2x=27; Combine the like terms. So, 3x=27; Now divide both sides of the equation by 3, therefore, x=9 which is the amt of fish Blair caught. So, 2(9)=18 is the amt of fish Jay caught. Check: 9 +2(9)=27; 27=27.</span>
Answer
<span>multiply by 2 and then add 5
1 x 2 + 5 = 2+5 =7
7 x 2 + 5 = 14 +5 = 19
19 x 2 +5 = 38 +5 = 43</span>
Answer:
3/4 times 3
Step-by-step explanation:
9/4 in fraction form, so it equal 2 1/4. Hope this helps
Answer:
Answer: Expression that represents the length of one side of the square is x - 5.